Tuning PID on Cascade Control Level Deareator Steam Power Plant - Bakhtiar Indra Kurniawan; Muhammad Haddin; Arief Marwanto (Universitas Islam Sultan Agung, 2018)
Deaerator is an important component in the process of steam power plant, which serves to remove gases contained in boiler water. The level of the deaerator tank should be maintained in accordance with the specified set point. If the level is too low it will effect to disrupt the performance of the boiler feed pump. If the level is too high it will lead to overflow and disrupt the steam production process. This study discusses the analysis of Proportional-Integral-Derivative (PID) cascade control using tuning Ziegler-Nichols (ZN) and Tyerus Luyben (TL) methods to control deaerator level. The tuning parameter in the primary loop and the secondary loop will be varied on the cascade loop control is used to analyze the performance of PID control. To perform verification system, such as Peak Time (Tp), Overshoot (Mp), Error Steady State (ESS) and Settling Time (Ts) a simulink Matlab is proposed. Four tuning PIDs on the cascade loop are: ZN-ZN, ZN-TL, TL-TL, TL-ZN get results that are able and get stability to follow the set point level. Tuning PID TL-TL method has the most ideal response result in use for deaerator level control at steam power plant because it has the lowest overshoot response of all three other cascade loop tuning methods. The transient response system has obtained values Tp=2,06 seconds, Mp=22,23%, Ess=0,7%, Ts=13,54 seconds.